Water management in Switzerland: decentralization, pragmatism, and fragmentation - Miranda, Graziele Muniz [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2021)
Switzerland has chosen not to adopt the current dominant model of integrated water resources management. Its type of federalism justifies it: decentralized, participatory and economically independent of international funding agencies. This article discusses, through literature review, the main features of the Swiss water management model according to its federal system. On the one hand, water policies are multiple, unique, decided and implemented locally. On the other hand, the main challenge refers to the horizontal interplay, related to the need for regionalization and coordination between uses.
Keywords: Integrated water resources management; Federalism; River basin; Participation